The Arkansas post of Louisiana - Arnold, Morris A. (University of Arkansas Press, 2017)
Arkansas Post, the first European settlement in what would become Jefferson?s Louisiana, had an important mission as the only settlement between Natchez and the Illinois Country, a stretch of more than eight hundred miles along the Mississippi River. The Post was a stopping point for shelter and supplies for those travelling by boat or land, and it was of strategic importance as well, as it nurtured and sustained a crucial alliance with the Quapaw Indians, the only tribe that occupied the region. The Arkansas Post of Louisiana covers the most essential aspects of the Post?s history, including the nature of the European population, their social life, the economy, the architecture, and the political and military events that reflected and shaped the Post?s mission.